ORGANIZATION OF MOVEMENT OF INFORMATION FLOWS IN PRAXEOLOGICAL AND CATALLACTICAL MODEL OF INFORMATIONAL SUPPORT OF STRATEGIC MANAGEMENT - Боярко , Ірина (Socio-economic relations in the digital society, 2019)
The article substantiates the need to organize accounting at enterprises under modern conditions on the basis of the praxeological and catallactical information support model. Necessary prerequisites for the formation of effective control systems are the ability to refl ect the eff ects of the internal and external environment through the organization of information flows. Th e organization of the movement of information flows in the praxeological and catallactical model of information provision of value-oriented strategic management should be carried out in compliance with the basic provisions of the cybernetic approach.Scientifi c requirements to the organization of the movement of information flows in the praxeological and catallactical model of information support for strategic management are defined.Management information circulates in the form of closed circuits that provide self-regulation of economic interactions and databases, aimed at building up experience and consolidating useful properties in data warehouses and using modern data mining technologies.The cybernetic scheme of the praxeological-cataclystic controlling model determines the peculiarities of the integration of the subsystems of the accounting-control and informational and analytical support of value-oriented strategic management. This scheme is an integrated combination of the four circuits of management information management. Depending on the level of interconnection of the subsystems of information support, it is possible to allocate to the contours of simple information circulation and outlines of the extended information circulation.